2004
DOI: 10.1590/s0036-36342004000500005
|View full text |Cite
|
Sign up to set email alerts
|

Políticas nacionales de salud y decisiones locales en México: el caso del Hospital Mixto de Cuetzalan, Puebla

Abstract: Our results confirmed that health organizations follow a historical process in which selected national and international forces open opportunities to promote intercultural health models that respond to the needs of indigenous populations. Despite the formerly held belief that traditional and scientific medicines were incompatible, this study demonstrates the viability of intercultural health care models that may become a real possibility in the country, based on new conventions to establish alternative and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
6
0
4
Order By: Relevance
“…Our results coincide with what other authors have described, that currently implemented policies in fact reproduce vertical models and frameworks, relationships of power-subordination among providers, etc. and are not reflective of models that fully integrate an intercultural vision [ 40 ]. Current policies only go so far as to promote the restructing of labor and delivery care for women, but without identifying pathways or processes for actually changing the practices that over-medicalize labor and delivery services in health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Our results coincide with what other authors have described, that currently implemented policies in fact reproduce vertical models and frameworks, relationships of power-subordination among providers, etc. and are not reflective of models that fully integrate an intercultural vision [ 40 ]. Current policies only go so far as to promote the restructing of labor and delivery care for women, but without identifying pathways or processes for actually changing the practices that over-medicalize labor and delivery services in health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, efforts to integrate Western and Indigenous medicine can result in greater access for vulnerable populations and more confidence in Western health services [4,7]. Intercultural health services have been shown to be successful when there is a mutual respect between the practitioners of both traditional and biomedical ‘medical’ systems [7,16,17]. This requires an exchange of information about practices and beliefs so that TBAs and health personnel teach and learn from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of Western and Indigenous medicine has been shown to result in increased confidence in western health services and to increase access for these vulnerable populations [4,7]. In Mexico there is a legal precedent for appropriate and respectful intercultural health services: the Mexican Constitution recognizes the use of traditional medicine as a cultural right and the Secretary of Health has an obligation to recognize, respect and promote the use of traditional medicine and adapt services to the needs and traditions of the indigenous population.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies demonstrated that medicinal plant use is not only limited to rural areas. Even medical institutions in urban areas of many developing countries have adopted and are using folk medicine as a form of complementary medicine to prevent or cure diseases [10][11][12].…”
Section: Introductionmentioning
confidence: 99%